Structural Insights Into the Effects of Interactions With Iron and Copper Ions on Ferritin From the Blood Clam Tegillarca granosa - Ming, Tinghong; Jiang, Qinqin; Huo, Chunheng; Huan, Hengshang; Wu, Yan; Su, Chang; Qiu, Xiaoting; Lu, Chenyang; Zhou, Jun; Li, Ye; Han, Jiaojiao; Zhang, Zhen; et al. (Frontiers in Molecular Biosciences, 2022)
In addition to its role as an iron storage protein, ferritin can function as a major detoxification component in the innate immune defense, and Cu2+ ions can also play crucial antibacterial roles in the blood clam, Tegillarca granosa. However, the mechanism of interaction between iron and copper in recombinant Tegillarca granosa ferritin (TgFer) remains to be investigated. In this study, we investigated the crystal structure of TgFer and examined the effects of Fe2+ and Cu2+ ions on the TgFer structure and catalytic activity. The crystal structure revealed that TgFer presented a typically 4–3–2 symmetry in a cage-like, spherical shell composed of 24 identical subunits, featuring highly conserved organization in both the ferroxidase center and the 3-fold channel. Structural and biochemical analyses indicated that the 4-fold channel of TgFer could be serviced as potential binding sites of metal ions. Cu2+ ions appear to bind preferentially with the 3-fold channel as well as ferroxidase site over Fe2+ ions, possibly inhibiting the ferroxidase activity of TgFer. Our results present a structural and functional characterization of TgFer, providing mechanistic insight into the interactions between TgFer and both Fe2+ and Cu2+ ions.